Increased shear stress- and ristocetin-induced binding of von Willebrand factor to platelets in cord compared with adult plasma - Rehak, Thomas; Cvirn, Gerhard; Gallistl, Siegfried; Leschnik, Bettina; Köstenberger, Martin; Katzer, Helga; Ribitsch, Volker; Muntean, Wolfgang (Thrombosis and Haemostasis, 2004)
Multiple indications do exist that the extensive neonatal platelet adhesion and aggregation, and the shorter closure time of neonatal compared with adult whole blood in the platelet function analyzer 100 are attributable to the physiological high plasma concentrations and high concentrations of unusually large von Willebrand factor (vWf) multimers in neonates. However, to date the direct experimental evidence is lacking. Therefore, we compared in the present study the ability of neonatal vWf to bind to platelets to that of adult vWf. Platelet-poor plasma of neonatal or adult origin, containing antibody-stained vWf, was incubated with neonatal or adult platelet suspension. Subsequently, vWf-platelet interaction was induced by exposing the mixture to shear stress by means of a cone/plate measuring system or by incubating the mixture with ristocetin. Finally, samples were analyzed in a FAC Scan flow cytometer. Detected fluorescence intensities directly correlate with the amount of vWf attached to the platelet surface. We found that significantly higher amounts of neonatal vWf were attached to platelets in the presence of shear stress or ristocetin.This efficient neonatal vWf-platelet interaction is an effect intrinsic to the neonatal vWf, and not to the neonatal platelet: the amount of neonatal vWf attached to neonatal platelets was not different from the amount of neonatal vWf attached to adult platelets. Furthermore, decreasing the vWf content in cord plasma to adult level resulted in significantly suppressed vWf-platelet attachment in the presence of ristocetin, indicating that the high neonatal vWf level contributes to the efficient vWf-platelet binding in neonates.
Keywords: Neonatal and adult platelets; von Willebrand factor; flow cytometry; shear stress